Co-processing and comprehensive utilization method for solid hazardous waste in aluminum industry

Through comprehensive disposal of aluminum industry solid waste, including roasting and reduction, iron removal and polymamu preparation process, the problem of harmless treatment and resource utilization of solid waste and resource utilization has been solved. A bybood.

CN119330406APending Publication Date: 2025-01-21YUNNAN HENGRUN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411517368.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Solid waste such as red mud, aluminum ash and cathode carbon blocks generated in the aluminum industry has problems of environmental pollution and resource waste, especially the alkali enrichment generated in the iron selection process of red mud has an impact on the environment.

Method used

Through comprehensive disposal of red mud, aluminum ash and cathode carbon pieces, the baking reduction process, iron removal process and polyum aluminum preparation process can be used to achieve harmless treatment of solid waste, and high -yield iron concentrates and polyte aluminum iron and other high Add value products.

Benefits of technology

The harmless treatment of aluminum industry solid waste, high -value added value products, reduced environmental pollution, and the process has the characteristics of green and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a co-processing and comprehensive utilization method for solid hazardous waste in the aluminum industry, and belongs to the technical field of industrial solid waste utilization, the method comprises the following steps: S1, roasting reduction process: uniformly mixing high-iron red mud, aluminum ash, cathode carbon blocks and an active additive, carrying out first-stage dry ball milling, and feeding a ball milling material into reduction roasting equipment for roasting; s2, an iron removal process is conducted, specifically, a reduction roasting product is subjected to second-stage wet ball milling again, slurry obtained after ball milling is subjected to wet reselection desliming, and iron ore concentrate, dehydration liquid and aluminum-silicon slag are obtained through magnetic separation; and S3, a poly-aluminum preparation process: mixing and reacting the silicon-aluminum slag, the aluminum-containing filtrate and hydrochloric acid to further prepare poly-aluminum ferric chloride, and recycling the poly-aluminum slag and the desliming slag to be used in the industries of brick making, cement building materials and the like. Meanwhile, high-added-value products such as iron ore concentrate and polyaluminum ferric chloride are produced as byproducts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of industrial solid waste utilization, and specifically relates to a method for coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry. Background Art

[0002] Red mud, aluminum ash and overhaul slag cathode carbon blocks are the three major solid hazardous wastes in the aluminum industry. Red mud is a high-alkali waste with large emissions and stockpiles, and contains valuable elements such as iron, aluminum, and silicon. Secondary aluminum ash contains metallic aluminum, aluminum oxide, aluminum nitride, aluminum carbide, magnesium aluminum spinel and other salts, which are toxic, reactive, and explosive when exposed to the environment. Overhaul slag cathode carbon powder mainly contains carbon, aluminum oxide, silicon oxide, silicate minerals, fluoride salts, etc. It has a high fluorine content and poses a great threat to the environment. Aluminum ash and overhaul slag are listed as hazardous wastes.

[0003] The common use of red mud is in the production of building materials such as bricks and cement. At present, there is increasing attention on the iron selection of red mud. Some companies directly recover iron concentrate from red mud through magnetic separation or magnetic roasting-magnetic separation process. The tailings left after iron selection are called red mud iron selection tailings. However, a large amount of alkali is enriched in the iron selection tailings during the red mud iron selection process, which has an impact on the environment. The red mud deep reduction iron selection group needs to add alkali, reducing agent, etc., which must cause the pressure of dealkalization at the back end. Therefore, after completing the full utilization of iron, aluminum, silicon, etc., it is a major problem to realize the harmless treatment of dealkalization at the same time, which is a major problem in the resource utilization of red mud iron selection. Aluminum ash contains alumina and 5-10% of elemental aluminum, and overhaul slag contains 60-70% of carbon. It can not only provide a reducing agent in coordination with red mud, but also extract aluminum, remove harmful elements, and realize the harmless treatment of aluminum ash and overhaul slag.

[0004] The present invention mainly realizes harmless treatment by comprehensively treating red mud, aluminum ash, cathode carbon blocks, defluorination and dealkalization, and produces high value-added products such as iron concentrate and polyaluminum ferric chloride as by-products. Summary of the invention

[0005] The purpose of the present invention is to provide a method for the coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry, to achieve comprehensive disposal of red mud, aluminum ash, and cathode carbon blocks, to achieve harmless disposal of solid wastes from the aluminum industry, and at the same time to produce high value-added products such as iron concentrate and polyaluminum ferric chloride. The method is green, efficient, and high value-added.

[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for coordinated disposal and comprehensive utilization of solid and hazardous wastes in the aluminum industry, comprising the following steps: Step S1: Calcination reduction process The high-iron red mud, aluminum ash, cathode carbon block and active additive are uniformly mixed and then subjected to the first stage of ball milling. The first stage of ball milling time is 30 to 60 minutes. After the first stage of ball milling is completed, a ball mill material is obtained. The size of the ball mill material is 100 to 300 meshes. The ball mill material is sent to a reduction roasting device and roasted for 1 to 2 hours at a roasting temperature of 1000 to 1300° C. to obtain a reduction roasting product. Step S2: Iron removal process The reduction roasting product is mixed with water in a ratio of 1: (5-10) to prepare a slurry with a slurry concentration of 200-300 g / L. The slurry is subjected to two-stage wet ball milling. The slurry after ball milling is subjected to spiral centrifugal gravity separation for 1-2 times. The coarse concentrate after gravity separation is subjected to wet gradient magnetic separation for 3-4 stages. After magnetic separation, the magnetic separation tailings, gravity separation slag, and iron concentrate slurry are subjected to solid-liquid separation to obtain iron concentrate dehydrated liquid. The iron concentrate is dried into iron concentrate powder using the waste heat of the reduction roasting equipment. Step S3: Polyaluminium Preparation Process The gravity separation slag, iron ore dehydration liquid and hydrochloric acid are prepared into a hydrochloric acid solution of a certain concentration, the hydrochloric acid concentration is 20-30%, the silicon aluminum slag and the prepared hydrochloric acid solution are reacted at 80-100°C to obtain a primary liquid, the reaction time is 1-2 hours, and then calcium aluminate powder is added to the primary liquid for polymerization reaction, the polymerization reaction temperature is 80-100°C, the reaction time is 1-2h, after the reaction is completed, the solid-liquid separation is carried out to obtain polyaluminium chloride ferric solution and polyaluminium slag.

[0007] Furthermore, the high-iron red mud has a main component of 40-50% Fe2O3, 20-25% Al2O3, 15-20% SiO2, 1-5% CaO, 8-15% Na2O, a particle size distribution of <75 μm, a main component ratio of 50-70%, other components of 30-50%, and a moisture content of <2%; the aluminum ash is secondary aluminum ash, and the main components are 5-15% AI, 60-80% Al2O3, 1-5% SiO2, and 1-3% Fe2O3; F The content is 2-5%, and the size is 80-100 mesh; the main components of the cathode carbon block are C content 60-70%, Na3AlF6 content 20-25%, NaF content 3-5%, Al2O3 content 3-6%, and particle size 1-5cm; the active additive is one or a combination of soda ash, sodium hydroxide, limestone, and calcium oxide; the mass components of the high-iron red mud, aluminum ash, cathode carbon block, and active additive are: red mud 60-70%, aluminum ash 5-10%, cathode carbon block 10-15%, and active additive 10-20%.

[0008] Furthermore, the total iron grade of the slurry after spiral centrifugal gravity separation is 25-30%; the iron grade of the gravity separation desludging slag is less than 10%, the Al2O3 content is 10-20%, the SiO2 content is 50-60%, and the CaO content is 20-30%.

[0009] Furthermore, in the wet gradient magnetic separation, the magnetic field strength of the first stage magnetic separation is 10000-15000 Gs; the magnetic field strength of the second stage magnetic separation is 8000-10000 Gs, and the magnetic field strength of the third stage magnetic separation is 5000-8000 Gs.

[0010] Furthermore, the iron concentrate grade is greater than 50%; the silicoalumina slag is the tailings and gravity separation slag after magnetic separation, and its components are Al2O3 content of 20-30%, SiO2 content of 40-50%, iron grade of less than 5%, and CaO content of 10-20%; the iron concentrate dehydration liquid has NaAlO2 content of 5-10% and SiO2 content of less than 0.005%.

[0011] Furthermore, the Al2O3 content in the polyaluminium ferric chloride is greater than 10%, the total iron mass fraction is 3-5%, and the basicity is 60-70%; and the soluble fluorine content in the polyaluminium slag is less than 20mg / L.

[0012] The beneficial effects of the present invention are embodied in: 1. Utilize 5-6% of elemental aluminum in aluminum ash to reduce iron oxide to elemental iron, and oxidize elemental aluminum to aluminum oxide, so as to avoid the subsequent process of aluminum reacting with water and hydrochloric acid to produce a large amount of hydrogen. At the same time, utilize the carbon in the cathode carbon block to reduce the non-magnetic iron in red mud to magnetic iron minerals and improve the reduction rate of iron; the addition of active additives can promote iron phase transformation and improve the reduction effect of magnetic iron.

[0013] 2. A part of the fluoride salts such as sodium fluoride and sodium fluoroaluminate in cathode carbon powder and aluminum ash is evaporated to recover sodium fluoride. During the calcination process, other fluoride salts react with calcium oxide to generate solidified fluorine to form insoluble calcium fluoride, aluminum hydroxide, etc., reducing the influence of fluoride on the dissolution process of aluminum oxide. At the same time, make full use of calcium in the active agent, calcium, sodium and other alkaline oxides in red mud to fix fluorine in aluminum ash and cathode carbon blocks to form solid calcium fluoride, sodium fluoride and other solids. Cyanide decomposes into carbon dioxide and nitrogen at high temperature in the furnace. Fluorine releases fluoride ions in the furnace and obtains calcium fluoride insoluble in calcium in red mud. Impurities such as calcium fluoride contained in iron concentrate can promote the effect of steel smelting. At the same time, calcium is used to convert sodium silicon slag into calcium silicon slag to achieve the effect of dealkalization, reduce the alkali content of iron concentrate, and inhibit silicon dissolution.

[0014] 3. In the pulping process, gravity separation and desludging are first carried out to improve the grade of iron concentrate, and then the slurry is subjected to gradient magnetic separation. The iron concentrate slurry is subjected to solid-liquid separation to reduce the alkaline substances in the iron concentrate. Two-stage grinding is adopted to expose the iron concentrate at the same time to improve the desludging effect. The gravity separation slag de-alkali liquid and the iron concentrate separation liquid are collected and fed into the polyaluminum preparation process to configure a certain concentration of hydrochloric acid to realize the resource utilization of waste liquid.

[0015] 4. Use waste heat to dry the iron ore concentrate to realize waste heat utilization. The obtained silicon aluminum slag can be used to prepare iron-containing polyaluminum chloride water purifier, while neutralizing and dealkalizing, reducing slag alkalinity, and making full use of aluminum and iron resources in the raw materials. The soluble fluorine content of the obtained polyaluminum slag is lower than the standard requirement, and can be further used to prepare building bricks.

[0016] 5. The present invention fully utilizes iron, aluminum, silicon in red mud, and carbon, silicon, aluminum fluoride, etc. in aluminum ash and overhaul slag to obtain products with certain added value, while achieving harmless treatment of solid waste. The final fluorine content of solid waste is lower than the standard requirement. DETAILED DESCRIPTION

[0017] The content of the present invention is further described below in conjunction with the examples. The examples are not intended to limit the scope of protection of the present invention. Without departing from the essence of the technical solution of the present invention, modifications or substitutions made to the method, steps or conditions of the present invention all belong to the scope of the present invention.

[0018] Unless otherwise specified, the equipment, devices and process methods used in the examples are conventional equipment, devices and process methods well known to those of ordinary skill in the art.

[0019] Example 1

[0020] The high-iron red mud used has a Fe2O3 content of 40%, an Al2O3 content of 25%, a SiO2 content of 20%, and a Na2O content of 15%. The particle size distribution is less than 75μm, accounting for 70%, the rest accounts for 30%, and the moisture accounts for 2.0%.

[0021] The aluminum ash used is secondary aluminum ash, with an AI metal content of 5%, an Al2O3 content of 60%, a SiO2 content of 5%, a Fe2O3 content of 3%, a F content of 5%, and a size of 80 mesh.

[0022] The waste cathode carbon block used has a C content of 60%, a Na3AlF6 content of 25%, a NaF content of 5%, an Al203 content of 6%, and a particle size of 5 cm.

[0023] A method for coordinated disposal and comprehensive utilization of solid and hazardous wastes in the aluminum industry, the method steps are as follows: Step S1: Calcination reduction process 65% of high-iron red mud, 10% of aluminum ash, 5% of cathode carbon block and 20% of active additives are uniformly mixed in proportion and then subjected to the first stage of ball milling. The first stage of ball milling time is 30 minutes. After the first stage of ball milling, a ball mill material is obtained. The size of the ball mill material is 120 meshes. The ball mill material is sent to a reduction roasting equipment and roasted for 1 hour at a roasting temperature of 1000°C to obtain a reduction roasting product. Step S2: Iron removal process The reduction roasting product was mixed with water in a ratio of 1:10 to prepare a slurry with a slurry concentration of 200 g / L. The slurry was subjected to two-stage wet ball milling. The particle size after ball milling was 200 mesh. The slurry after ball milling was subjected to spiral centrifugal gravity separation once. The total iron grade after gravity separation was 25%. The rough concentrate after gravity separation was then subjected to wet gradient magnetic separation. The magnetic separation was carried out in three stages. The magnetic field strength of the first stage was 10000 Gs, the magnetic field strength of the second stage was 8000 Gs, and the magnetic field strength of the third stage was 5000 Gs. Gs, the total iron grade of the iron concentrate after magnetic separation is >50%, and the alkali content (sodium oxide equivalent) is 5%, of which the total iron grade of the concentrate is >70%, accounting for 50%; the total iron grade of the concentrate is >60%, accounting for 70%; after magnetic separation, the magnetic separation tailings, gravity separation slag, and iron concentrate slurry are separated into solid and liquid to obtain the iron concentrate dehydrated liquid, and the iron concentrate is dried into iron concentrate powder by using the waste heat of the reduction roasting equipment. The tailings and gravity separation slag after magnetic separation have an average Al203 content of 20% and a Fe2O3 content of 10%; the NaAlO2 content of the dehydrated liquid is 10%, and the SiO2 content is 0.005%; Step S3: Polyaluminium Preparation Process The gravity separation slag, iron ore dehydration liquid and hydrochloric acid are prepared into a hydrochloric acid solution of a certain concentration, the hydrochloric acid concentration is 20%, the silicon aluminum slag and the prepared hydrochloric acid solution are reacted at 80°C to obtain a primary liquid, the reaction time is 1 hour, and then calcium aluminate powder is added to the primary liquid for polymerization reaction, the polymerization reaction temperature is 80°C, the reaction time is 1 hour, after the reaction is completed, the solid-liquid separation is carried out to obtain polyaluminium chloride ferric solution and polyaluminium slag.

[0024] The obtained polyaluminium ferric chloride has an Al2O3 content of 10%, a total iron mass fraction of 5%, a basicity of 60%, and other properties meet the standard requirements of "Polyaluminium Chloride for Water Treatment Agents" (GB / T22627-2022). The soluble fluorine content of the obtained polyaluminium solid slag is 20mg / L, which meets the standards for building materials.

[0025] Table 1 Effect of Example 1 Example 2 The high-iron red mud used has a Fe2O3 content of 43%, an Al2O3 content of 23%, a SiO2 content of 18%, and a Na2O content of 13%. The particle size distribution is less than 75μm, accounting for 55%, the rest accounts for 45%, and the moisture accounts for 1.5%.

[0026] The aluminum ash used is secondary aluminum ash, with AI metal content of 8%, Al2O3 content of 65%, SiO2 content of 4%, Fe2O3 content of 2.5%; F content of 4%, size of 85 mesh.

[0027] The waste cathode carbon block used has a C content of 65%, a Na3AlF6 content of 23%, a NaF content of 4%, an Al203 content of 5%, and a particle size of 4 cm.

[0028] A method for coordinated disposal and comprehensive utilization of solid and hazardous wastes in the aluminum industry, the method steps are as follows: Step S1: Calcination reduction process 68% of high-iron red mud, 8% of aluminum ash, 7% of cathode carbon block and 17% of active additives were uniformly mixed in proportion and then subjected to the first stage of ball milling. The first stage of ball milling lasted for 40 minutes. After the first stage of ball milling, a ball mill material was obtained. The size of the ball mill material was 180 meshes. The ball mill material was sent to a reduction roasting equipment and roasted for 1.5 hours at a roasting temperature of 1100°C to obtain a reduction roasting product. Step S2: Iron removal process The reduction roasting product was mixed with water in a ratio of 1:8 to prepare a slurry with a slurry concentration of 250 g / L. The slurry was subjected to two-stage wet ball milling. The particle size after ball milling was 250 mesh. The slurry after ball milling was subjected to spiral centrifugal gravity separation once. The total iron grade after gravity separation was 27%. The rough concentrate after gravity separation was then subjected to wet gradient magnetic separation. The magnetic separation was carried out in three stages. The magnetic field strength of the first stage was 12000 Gs, the magnetic field strength of the second stage was 8500 Gs, and the magnetic field strength of the third stage was 6000 Gs. Gs, the total iron grade of the iron concentrate after magnetic separation is >53%, and the alkali content (sodium oxide equivalent) is 4%, of which the total iron grade of the concentrate is >70%, accounting for 55%; the total iron grade of the concentrate is >60%, accounting for 75%; after magnetic separation, the magnetic separation tailings, gravity separation slag, and iron concentrate slurry are separated into solid and liquid to obtain the iron concentrate dehydrated liquid, and the iron concentrate is dried into iron concentrate powder by using the waste heat of the reduction roasting equipment. The average Al2O3 content of the tailings and gravity separation slag after magnetic separation is 25%, and the Fe2O3 content is 8%; the NaAlO2 content of the dehydrated liquid is 8%, and the SiO2 content is less than 0.004%; Step S3: Polyaluminium Preparation Process The gravity separation slag, iron ore dehydration liquid and hydrochloric acid are prepared into a hydrochloric acid solution of a certain concentration, the hydrochloric acid concentration is 25%, the silicon aluminum slag and the prepared hydrochloric acid solution are reacted at 85°C to obtain a primary liquid, the reaction time is 1.5 hours, and then calcium aluminate powder is added to the primary liquid for polymerization reaction, the polymerization reaction temperature is 85°C, the reaction time is 1.5h, after the reaction is completed, the solid-liquid separation is carried out to obtain polyaluminium chloride ferric solution and polyaluminium slag.

[0029] The obtained polyaluminium ferric chloride has an Al2O3 content of 11%, a total iron mass fraction of 4.5%, a basicity of 65%, and other properties meet the standard requirements of "Polyaluminium Chloride for Water Treatment Agents" (GB / T22627-2022). The soluble fluorine content of the obtained polyaluminium solid slag is 18mg / L, which meets the standards for building materials.

[0030] Table 2 Example 2 Effect Example 3 The high-iron red mud used has a Fe2O3 content of 48%, an Al2O3 content of 21%, a SiO2 content of 16%, and a Na2O content of 10%. The particle size distribution is less than 75μm, accounting for 58%, the rest accounts for 42%, and the moisture accounts for 1.0%.

[0031] The aluminum ash used is secondary aluminum ash, with an AI metal content of 10%, an Al2O3 content of 75%, a SiO2 content of 3%, a Fe2O3 content of 2.0%, a F content of 3%, and a size of 90 mesh.

[0032] The waste cathode carbon block used has a C content of 68%, a Na3AlF6 content of 21%, a NaF content of 3.5%, an Al203 content of 4%, and a particle size of 3 cm.

[0033] A method for coordinated disposal and comprehensive utilization of solid and hazardous wastes in the aluminum industry, the method steps are as follows: Step S1: Calcination reduction process 72% of high-iron red mud, 7% of aluminum ash, 8% of cathode carbon block and 13% of active additives were uniformly mixed in proportion and then subjected to the first stage of ball milling. The first stage of ball milling lasted for 50 minutes. After the first stage of ball milling, a ball mill material was obtained. The size of the ball mill material was 240 meshes. The ball mill material was sent to a reduction roasting equipment and roasted for 2 hours at a roasting temperature of 1200°C to obtain a reduction roasting product. Step S2: Iron removal process The reduction roasting product was mixed with water in a ratio of 1:6 to prepare a slurry with a slurry concentration of 280 g / L. The slurry was subjected to two-stage wet ball milling. The particle size after ball milling was 280 mesh. The slurry after ball milling was subjected to spiral centrifugal gravity separation twice. The total iron grade after gravity separation was 29%. The rough concentrate after gravity separation was then subjected to wet gradient magnetic separation. The magnetic separation was carried out in three stages. The magnetic field strength of the first stage was 13000 Gs, the magnetic field strength of the second stage was 9000 Gs, and the magnetic field strength of the third stage was 7000 Gs. Gs, the total iron grade of the iron concentrate after magnetic separation is greater than 55%, and the alkali content (sodium oxide equivalent) is 3%, of which the total iron grade of the concentrate is greater than 70%, accounting for 60%; the total iron grade of the concentrate is greater than 60%, accounting for 78%; after magnetic separation, the magnetic separation tailings, gravity separation slag, and iron concentrate slurry are separated into solid and liquid to obtain the iron concentrate dehydrated liquid, and the iron concentrate is dried into iron concentrate powder by using the waste heat of the reduction roasting equipment. The tailings and gravity separation slag after magnetic separation have an average Al203 content of 28% and a Fe2O3 content of 6%; the NaAlO2 content of the dehydrated liquid is 6%, and the SiO2 content is less than 0.003%; Step S3: Polyaluminium Preparation Process The gravity separation slag, iron ore dehydration liquid and hydrochloric acid are prepared into a hydrochloric acid solution of a certain concentration, the hydrochloric acid concentration is 28%, the silicon aluminum slag and the prepared hydrochloric acid solution are reacted at 88°C to obtain a primary liquid, the reaction time is 1.8 hours, and then calcium aluminate powder is added to the primary liquid for polymerization reaction, the polymerization reaction temperature is 90°C, the reaction time is 1.8h, after the reaction is completed, the solid-liquid separation is carried out to obtain polyaluminium chloride ferric solution and polyaluminium slag.

[0034] The obtained polyaluminium ferric chloride has an Al2O3 content of 11.5%, a total iron mass fraction of 4%, a basicity of 68%, and other properties meet the standard requirements of "Polyaluminium Chloride for Water Treatment Agents" (GB / T22627-2022). The soluble fluorine content of the obtained polyaluminium solid slag is 15mg / L, which meets the standards for building materials.

[0035] Table 3 Effect of Example 3 Example 4 The high-iron red mud used has a Fe2O3 content of 50%, an Al2O3 content of 20%, a SiO2 content of 15%, and a Na2O content of 8%. The particle size distribution is less than 75μm, accounting for 60%, the rest accounts for 40%, and the moisture accounts for 0.8%.

[0036] The aluminum ash used is secondary aluminum ash, with an AI metal content of 15%, an Al2O3 content of 80%, a SiO2 content of 1%, a Fe2O3 content of 1%, a F content of 2%, and a size of 100 mesh.

[0037] The waste cathode carbon block used has a C content of 70%, a Na3AlF6 content of 20%, a NaF content of 3%, an Al203 content of 3%, and a particle size of 1 cm.

[0038] A method for coordinated disposal and comprehensive utilization of solid and hazardous wastes in the aluminum industry, the method steps are as follows: Step S1: Calcination reduction process 75% of high-iron red mud, 5% of aluminum ash, 10% of cathode carbon block and 10% of active additives were uniformly mixed in proportion and then subjected to the first stage of ball milling. The first stage of ball milling lasted for 60 minutes. After the first stage of ball milling, a ball mill material was obtained. The size of the ball mill material was 300 meshes. The ball mill material was sent to a reduction roasting equipment and roasted for 2 hours at a roasting temperature of 1300°C to obtain a reduction roasting product. Step S2: Iron removal process The reduction roasting product was mixed with water in a ratio of 1:5 to prepare a slurry with a slurry concentration of 300 g / L. The slurry was subjected to two-stage wet ball milling. The particle size after ball milling was 300 mesh. The slurry after ball milling was subjected to spiral centrifugal gravity separation twice. The total iron grade after gravity separation was 30%. The rough concentrate after gravity separation was then subjected to wet gradient magnetic separation. The magnetic separation was carried out in three stages. The magnetic field strength of the first stage was 15000 Gs, the magnetic field strength of the second stage was 10000 Gs, and the magnetic field strength of the third stage was 8000 Gs. Gs, the total iron grade of the iron concentrate after magnetic separation is >58%, and the alkali content (sodium oxide equivalent) is 3%, of which the total iron grade of the concentrate is >70%, accounting for 70%; the total iron grade of the concentrate is >60%, accounting for 80%; after magnetic separation, the magnetic separation tailings, gravity separation slag, and iron concentrate slurry are separated into solid and liquid to obtain the iron concentrate dehydrated liquid, and the iron concentrate is dried into iron concentrate powder by using the waste heat of the reduction roasting equipment. The tailings and gravity separation slag after magnetic separation have an average Al2O3 content of 30% and a Fe2O3 content of 5%; the NaAlO2 content of the dehydrated liquid is 5%, and the SiO2 content is 0.002%; Step S3: Polyaluminium Preparation Process The gravity separation slag, iron ore dehydration liquid and hydrochloric acid are prepared into a hydrochloric acid solution of a certain concentration, the hydrochloric acid concentration is 30%, the silicon aluminum slag and the prepared hydrochloric acid solution are reacted at 90°C to obtain a primary liquid, the reaction time is 2 hours, and then calcium aluminate powder is added to the primary liquid for polymerization reaction, the polymerization reaction temperature is 100°C, the reaction time is 2h, after the reaction is completed, the solid-liquid separation is carried out to obtain polyaluminium chloride ferric solution and polyaluminium slag.

[0039] The obtained polyaluminium ferric chloride has an Al2O3 content of 12%, a total iron mass fraction of 3%, a basicity of 70%, and other properties meet the standard requirements of "Water Treatment Agent Polyaluminium Chloride" (GB / T22627-2022). The obtained polyaluminium solid slag has a soluble fluorine content of 12mg / L, which meets the standards for building materials.

[0040] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

Claims

1. A method for the coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry, characterized in that , the method comprises the following steps: Step S1: Calcination reduction process The high-iron red mud, aluminum ash, cathode carbon block and active additive are uniformly mixed and then subjected to the first stage of ball milling. The first stage of ball milling time is 30 to 60 minutes. After the first stage of ball milling is completed, a ball mill material is obtained. The size of the ball mill material is 100 to 300 meshes. The ball mill material is sent to a reduction roasting device and roasted for 1 to 2 hours at a roasting temperature of 1000 to 1300° C. to obtain a reduction roasting product. Step S2: Iron removal process The reduction roasting product is mixed with water in a ratio of 1: (5-10) to prepare a slurry with a slurry concentration of 200-300 g / L. The slurry is subjected to two-stage wet ball milling. The slurry after ball milling is subjected to spiral centrifugal gravity separation for 1-2 times. The coarse concentrate after gravity separation is subjected to wet gradient magnetic separation for 3 stages. After magnetic separation, the magnetic separation tailings, gravity separation slag, and iron concentrate slurry are subjected to solid-liquid separation to obtain iron concentrate dehydrated liquid. The iron concentrate is dried into iron concentrate powder using the waste heat of the reduction roasting equipment. Step S3: Polyaluminium Preparation Process The gravity separation slag, iron ore dehydration liquid and hydrochloric acid are prepared into a hydrochloric acid solution of a certain concentration, the hydrochloric acid concentration is 20-30%, the silicon aluminum slag and the prepared hydrochloric acid solution are reacted at 80-100°C to obtain a primary liquid, the reaction time is 1-2 hours, and then calcium aluminate powder is added to the primary liquid for polymerization reaction, the polymerization reaction temperature is 80-100°C, the reaction time is 1-2h, after the reaction is completed, the solid-liquid separation is carried out to obtain polyaluminium chloride ferric solution and polyaluminium slag.

2. The method for coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry according to claim 1, characterized in that: The main components of the high-iron red mud are Fe2O3 content of 40-50%, Al2O3 content of 20-25%, SiO2 content of 15-20%, CaO content of 1-5%, Na2O content of 8-15%, particle size distribution of <75μm, main components account for 50-70%, others account for 30-50%, and moisture content is <2%; the aluminum ash is secondary aluminum ash, the main components are AI content of 5-15%, Al2O3 content of 60-80%, SiO2 content of 1-5%, Fe2O3 content of 1-3%; F content of 2- 5%, size 80-100 mesh; the main components of the cathode carbon block are C content 60-70%, Na3AlF6 content 20-25%, NaF content 3-5%, Al2O3 content 3-6%, and particle size 1-5cm; the active additive is one or a combination of soda ash, sodium hydroxide, limestone, and calcium oxide; the mass components of the high-iron red mud, aluminum ash, cathode carbon block, and active additive are: high-iron red mud 60-70%, aluminum ash 5-10%, cathode carbon block 10-15%, and active additive 10-20%.

3. The method for coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry according to claim 1, characterized in that: The total iron grade of the slurry after spiral centrifugal gravity separation is 25-30%; the iron grade of the gravity separation desludging slag is less than 10%, the Al2O3 content is 10-20%, the SiO2 content is 50-60%, and the CaO content is 20-30%.

4. The method for coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry according to claim 1, characterized in that: In the wet gradient magnetic separation, the magnetic field strength of the first stage magnetic separation is 10000-15000 Gs; the magnetic field strength of the second stage magnetic separation is 8000-10000 Gs, and the magnetic field strength of the third stage magnetic separation is 5000-8000 Gs.

5. The method for coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry according to claim 1, characterized in that: The iron concentrate grade is greater than 50%; the silicoalumina slag is the tailings and gravity separation slag after magnetic separation, and its components are Al2O3 content of 20-30%, SiO2 content of 40-50%, iron grade of less than 5%, and CaO content of 10-20%; the iron concentrate dehydration liquid has NaAlO2 content of 5-10% and SiO2 content of less than 0.005%.

6. The method for coordinated disposal and comprehensive utilization of solid and hazardous wastes from the aluminum industry according to claim 1, characterized in that: The Al2O3 content in the polyaluminium ferric chloride is greater than 10%, the total iron mass fraction is 3-5%, and the basicity is 60-70%; the soluble fluorine content in the polyaluminium slag is less than 20mg / L.

Citation Information

Cited By

  • Method for removing heavy metals in waste incineration fly ash

    CN119870129A

  • Method for comprehensively treating high-iron low-silicon red mud through alkali magnetization roasting

    CN120099279A